The Influence Of Brand image In Influenced Health Care Facilities Selection Decisions At Adi Husada Hospital, Kapasari - Valencia Putri Junaedi; Afif Kurniawan; Dwi Yuniar Ramadhani; Dina Astiana (Jurnal Kesehatan dan Kedokteran, 2025)
Brand image is a consumer's view of an institution, which will influence a patient's decision to choose a health service. The dimensions of brand image include 4 components, namely corporate identity, physical environment, contact personnel, and service offerings. The purpose of this study was to determine the role of brand image on patient decisions in the process of selecting health facility services at Adi Husada Hospital Surabaya. This study used a quantitative approach with a survey method. The sample in this study were patients at Adi Husada Kapasari Hospital with inclusion criteria of over 18 years old and general outpatients. This study used a logistic regression test as a tool to determine the effect on patient care. The results of the study obtained a p-value of 0.000 (<0.05) indicating a significant influence on patient decisions at Adi Husada Kapasari Hospital Surabaya. This shows that brand image can influence patient decisions in choosing health facilities. Brand image can be used as information and reinforcement as a basis for determining patient decisions in choosing health facilities, the better the brand image that arises in a person's perception, the stronger it will be to be used as a decision maker. This study can be concluded that there is a significant influence between brand image measured through corporate identity, physical environment, contact personnel, and service offerings. The p value of 0.000 (<0.05) indicates that brand image influences decision making.